Estudo comparativo entre a fixação interna rígida com parafuso compressivo tipo neck screw e microplacas com microparafusos nas fraturas do complexo zigomático - Omizzolo, Guilherme (2012)
The tetraploid fractures from the zygomatic complex need accuracy in the correction and an efficient internal fixation for obtaining a good final result. Aiming at improving the advantages and minimizing the disadvantages of the rigid internal techniques, the screw "Neck Screw" was developed. The necessary stability for the correct fixation comes from a dynamic compression sistem increasing the contact between the stumps fractured. This assignment has the objectives to evaluate: the fixation and the stability of the dysjunction-fractures of the zygomatic complex provided by the screw "Neck Screw", applied in the region of the frontozygomatic suture, and to compare with a technique already devoted of micro-plaques and micro-screws applied in the region of the frontozygomatic suture and edge of inferior orbit; the after-operative confort or the disconfort reported by the pacient; the medium medical-surgical time used. To evaluate the efficiency of the screw "Neck Screw", thirty pacients with tetraploid fractures of zygoma had their computerized tomographies done on axial and coronale cuts for evidencing the fractures and for surgical planning. The pacients were subjected to the surgical procedure with osteosynthesis through the "Neck Screw" and the micro-plaque and micro-screw technique in the frontozygomatic region, having the surgical time properly noted. After 24 hours and 30 days, they were subjected to a new tomographic exam. The results gotten and measuremented were subjected to statistical tests of Mann Whitney, among the techniques used, and test T for the time. The importance of this research lies on the proposal of a technique for the reduction and fixation of the disjunction-fractures of the zygomatic complex minimally invasive in relation to the other techniques compared in the literature. The technique with the screw, "Neck Screw", guarantees stability of the fixation through the tomographic follow up. The analysis of the statistic about the measurements was revealed highly significant. The pacients' clinic follow up showed us absense of facial asymmetry, enophthalmos or diplopia. The operating time is significantly reduced and there is decrease of the disconfort reported by the pacients when palpating on the frontzygomatic region, thus the screw, "Neck screw", has an intra-osseous housing.